Why I am not a Calvinist - Walls, Jerry L.; Dongell, Joseph (Downers Grove, Ill. : InterVarsity Press, 2004)
What's wrong with Calvinism? Since the Reformation, Calvinism has dominated much of evangelical thought. It has been so well established that many Christians simply assume it to be the truest expression of Christian doctrine. But Calvinism has some serious biblical and theological weaknesses that unsettle laypeople, pastors and scholars alike. God is sovereign. All evangelical Christians--whether Arminians or Calvinists--have no doubt about this fundamental truth. But how does God express his sovereignty? Is God a master puppeteer, pulling our strings? Or has he graciously given his children freedom to respond to his love? In this eminently readable book, Jerry L. Walls and Joseph R. Dongell explore the flaws of Calvinist theology. Why I Am Not a Calvinist is a must-read for all who struggle with the limitations of this dominant perspective within evangelical theology. - Back cover.
Approaching the Bible -- Engaging the Bible -- Calvinism and the nature of human freedom -- Calvinism and divine sovereignty -- Calvinism and consistency -- Calvinism and the Christian life.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Calvinism; Calvinisme; Systematische theologie; Calvinism; RELIGION / Christian Theology / Systematic; RELIGION / Christianity / General; Electronic books